Pengaruh Pendapatan Perkapita, Suku Bunga, Populasi dan Zakat Terhadap Tingkat Konsumsi Rumah Tangga di Indonesia - Zarkasi Zarkasi; Lidya Hidayah (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The phenomenon of consumption levels in Indonesia is an important concern today. This is suspected or proven by non-economic economic factors. In this study, the factors that become exogenous variables in the observation include per capita income, interest rates, population and zakat distribution. This analysis uses descriptive and associative methods to fully describe each variable and also the relationship between exogenous variables and endogenous variables in the form of consumption levels. The data used is in the form of a data panel with data crosses six times with observation time from 2013 to 2018. The results of this study indicate that partially per capita income, population and zakat have a positive and significant effect on the level of household consumption in Indonesia. Meanwhile, the interest rate has a negative and significant effect on the Household Consumption Level in Indonesia.